Coronary flow reserve as a link between exercise capacity, cardiac systolic and diastolic function. (15th August 2016) - Blomster, Juuso I.; Svedlund, Sara; U.Westergren, Helena; Gan, Li-Ming
Abstract: Background: Decreased coronary flow reserve (CFR) is associated with increased risk of adverse cardiovascular events. We sought to investigate how CFR from left anterior descending (LAD) coronary artery reflects clinical markers of cardiac function. Methods: We enrolled 400 patients referred for myocardium perfusion scintigraphy due to chest pain at Sahlgrenska University Hospital in Gothenburg, Sweden. Transthoracic echocardiography including adenosine-assisted CFR in LAD was performed at a separate occasion. Results: Median age was 62 years (range 32–83) and 47% were female. Prior myocardial infarction had occurred in 28% of the population. In adjusted multivariate models, CFR in LAD was associated with echocardiography left ventricle ejection fraction at rest (β = 0.97, p = 0.033) as well as under stress (β = 1.52, p = 0.0056) and maximum exercise capacity (β = 6.27, p = 0.026). CFR in LAD outweighed left ventricle ejection fraction as the determinant of maximum exercise capacity. Hyperaemic diastolic mitral annulus peak velocity measured by vector velocity imaging was inversely associated with LAD CFR (β = − 0.39, p = 0.0077). In subgroup analyses these findings were associated with normal coronary perfusion in myocardium perfusion scintigraphy. Conclusions: In patients with angina-like symptoms CFR measured in LAD reflects well both systolic and diastolic cardiac function emphasizing the essential role of myocardial microvascular circulation in cardiac physiology.